Comparison of the Effect of Yoghurt Starter Bacteria and Lactobacillous Bulgaricus on Peripheral Blood Mononuclear Cells Activity of Ulcerative Colitis Patients - A Sheikhi; Z Ahmadi; M Askari (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2018)
BACKGROUND AND OBJECTIVE: Ulcerative colitis is an inflammatory bowel disease and involving colon and rectum. Since patients with ulcerative colitis have high levels of pro-inflammatory and anti-inflammatory cytokines, the aim of this study was to compare the effects of starter bacteria of yogurt and lactobacillus boulagaricus on the activity of peripheral blood mononuclear cells in patients with ulcerative colitis. METHODS: This experimental-laboratory study was performed on 10 ulcerative colitis patients in Dezful, Andimeshk and Shoosh in two experimental groups and a control group. Experimental groups included co-culture of PBMC and intended bacteria in dilutions of 0.1 and 0.01 and at 48 and 72 hours, and control group including PBMC of the patient at 48 and 72 hours. Variables IL-10 and IL-1β) were measured by ELISA. FINDINGS: There was a significant increase in the secretion of IL1β at dilution of 0.1 and 48 hours by PBMC stimulated with bulgaricus 940.4±249.61 in comparison with the starter 669.12±181.11 (p=0.004) and in 72 hours by bulgaricus 796.3±213.34 in comparison with the starter 464.25±128.41 (p=0.000), In dilution of 0.01 and 48 hours by bulgaricus 747.5±198.54 in comparison with starter 529.25±163.82 (p=0.005) and in 72 hours by bulgaricus 617.4±192.5 in comparison with starter 408.62±134.78 (P=0.004). Also, there was a significant increase in the secretion of cytokines in both dilution and both times between of the experimental groups and control. CONCLUSION: The results of the study showed that Lactobacillus bulgaricus causes inflammation in comparison with the starter by IL1β secretion. Starter bacteria has a better role in reducing inflammation.